Pengaruh Interaksi Komunikasi Perempuan Double Burden Terhadap Keluarga Patriarki Batak Karo - Citra Mayang Sari; Anang Anas Azhar (Unitri Press, 2023)
Double burden is a double burden that is carried by women to work for a living and play a big role as housewives. The objectives of this study are: 1) knowing the communication interaction of double burden women in the patriarchal family of Dolat Rayat village, 2) knowing the communication interaction of the patriarchal family of Dolat Rayat village with double burden women and 3) knowing the influence of the interaction of double burden women's communication with the patriarchal family of Dolat Rayat village. This research is a quantitative research with a correlational method. Through the results of the first percentage analysis, an average percentage of 74.69% was obtained in the interval of 60%-80% with good criteria. This shows that there is a good communication interaction carried out by barden women (wives) in the patriarchal family environment. While the results of the second percentage analysis obtained an average percentage of 64.63% entering the interval of 60%-80% with good criteria, meaning that the interaction of patriarchal family communication (husband) with double burden women (wives) did not occur a significant problem Furthermore, through the results of the correlation ụji analysis, a correlation coefficient (r) value of 0.648 was obtained, indicating that there was a strong influence on the communication interaction of double burden women (wives) with the patriarchal family (husband) in the village. Abstrak Double burden merupakan beban ganda yang dipinggul oleh perempuan untuk bekerja mencari nafkah serta berperan besar sebagai ibu rumah tangga. Tujuan penelitian ini yaitu: 1) mengetahui interaksi komunikasi perempuan double burden(istri) dengan keluarga patriarki Desa Dolat Rayat, 2) mengetahui interaksi komunikasi keluarga patriarki (suami) Desa Dolat Rayat dengan perempuan double burden (istri) dan 3) mengetahui hubungan interaksi komunikasi perempuan double burden (istri) dengan keluarga patriarki (suami) Desa Dolat Rayat. Penelitian ini merupakan penelitian kuantitatif dengan jenis metode korelasional. Melalui hasil analisis persentase pertama diperoleh rata-rata persentase data interaksi komunikasi perempuan double burden (istri) sebesar 74,69% masuk interval 60%-80% dengan kriteria baik. Ini menunjukkan bahwa adanya interaksi komunikasi yang baik dilakukan oleh perempuan burden (istri) di lingkungan keluarga patriarki. Sedangkan hasil analisis persentase kedua diperoleh rata-rata persentase data interaksi komunikasi keluarga patriarki (suami) sebesar 64,63% masuk interval 60%-80% dengan kriteria baik, artinya interaksi komunikasi keluarga patriarki (suami) dengan perempuan double burden (istri) tidak terjadi sebuah permasalahan yang berarti Selanjutnya melalui hasil analisis ụji korelasi diperoleh nilai koefisien korelasi (r) sebesar 0,648, menunjukkan bahwa adanya pengaruh yang kuat interaksi komunikasi perempuan double burden (istri) dengan keluarga patriarki (suami) di Desa tersebut.